The People I Know - Zafris, Nancy (Book collections on Project MUSE., 1990)
The People I Know is a collection of nine stories, told by characters who hover at the edge of life. Whether it's Lorne, perched on a sofa as a wedding party swirls around him, or the elderly Mrs. R of ""Morning at the Beach, "" imagining a career in crime as she sits on the front porch of a Miami hotel, these are people oddly accustomed to the sidelines of their worlds. Nancy Zafris's characters do not so much hurdle their barriers as contemplate them with varying degrees of humor, regret, and fanciful expectation. Gazing out of his window at a horizon of crushed cars, Bonner Junior fantasizes.